ENDOPHYTIC FUNGAL ASSISTED SYNTHESIS OF SILVER NANOPARTICLES, CHARACTERIZATION AND ANTIMICROBIAL ACTIVITY - Netala, Vasudeva Reddy; Ghosh, Sukhendu Bikash; Bobbu, Pushpalatha; Tartte, Vijaya (Asian Journal of Pharmaceutical and Clinical Research, 2015)
Objective: The objective was to investigate the biosynthesis of silver nanoparticles (SNPs) using extracellular fungal filtrate of Aspergillus niger and check their antimicrobial activity against Staphylococcus aureus and Escherichia coli. Methods: 10 ml of extracellular fungal filtrate of A. niger was added to 50 ml of 1 mM silver nitrate and incubated at room temperature for 24 hrs. SNPs were characterized using ultraviolet-visible (UV-Vis) spectroscopy, Fourier transforms infrared spectroscopy (FTIR), transmission electron microscopy (TEM), atomic force microscopy (AFM), and X-ray diffraction analysis (XRD). Antimicrobial activity was checked against S. aureus and E. coli by employing disc diffusion method. Results: The color change of the solution from light yellow to dark brown indicated the formation of SNPs. The formation of SNPs was further confirmed by UV-Vis spectroscopy, which showed the characteristic peak between 400 and 460 nm. TEM and AFM analysis showed that the size of SNPs were between 10 and 50 nm with roughly spherical in shape. XRD analysis confirmed the crystalline nature of SNPs synthesized by showing the Braggs peaks which could be indexed to (111) and (220) of face cubic crystal phase of silver. FTIR showed the peaks at 1026, 1215, 1348, 1632, and 2928/cm, which were responsible for the different functional groups possibly involved in the synthesis and stabilization of SNPs. The SNPs formed the inhibition zones of 14.0 and 12.5 mm against S. aureus and E. coli, respectively. Conclusion: It is concluded that the biosynthesis of SNPs using extracellular fungal filtrate of A. niger was simple, eco-friendly, and robust. The SNPs synthesized were well-dispersed, crystalline in nature and also proved to be excellent antimicrobial agents. Keywords: Silver nanoparticles, Aspergillus niger, Transmission electron microscopy, X-ray diffraction, Antimicrobial activity.